HELPING RELATIONSHIP BETWEEN COUNSELOR AND CLIENT (STRUCTURING, TRANSFERANCE, COUNTERTRANFERENCE) - Lika Lika; Yeni Karneli; Rezki Hariko (Widyagogik, 2022)
Human relationships have very many elements of aid. This is very much needed because of various conditions such as experiencing dilemmas, disputes, and crises felt by individuals who need immediate help. The success of counseling is largely determined by the effectiveness of a counselor in using various techniques to help individuals who have problems. Therefore, a counselor should be able to explore and apply various techniques in creating a relationship between the counselor and his client.